2010
DOI: 10.1158/1055-9965.epi-09-0660
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glucosinolate Intake, Polymorphisms in Selected Biotransformation Enzymes, and Risk of Prostate Cancer

Abstract: A protective role of glucosinolates in prostate cancer development might be mediated by the induction of biotransformation enzymes. These enzymes, enhancing the elimination of carcinogens from the body, are known to be polymorphic. Therefore, we evaluated whether a possible association between glucosinolate intake and prostate cancer risk is modified by polymorphisms in GSTT1, GSTM1, GSTA1, GSTP1, or NOQ1 genes. A case-control study including 248 prostate cancer cases and 492 matched controls was nested in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 26 publications
2
34
0
4
Order By: Relevance
“…The associations between gene polymorphisms and prostate cancer risk (main effects) were reported earlier [21][22] and are thus not shown here. The allele frequencies of the selected genetic variants in PCa cases and controls are shown in Table 2.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The associations between gene polymorphisms and prostate cancer risk (main effects) were reported earlier [21][22] and are thus not shown here. The allele frequencies of the selected genetic variants in PCa cases and controls are shown in Table 2.…”
Section: Resultsmentioning
confidence: 76%
“…As a consequence, increased expression and metabolic activation of CYP1A1, CYP1A2 and CYP1B1 has been shown in benign prostatic hyperplasia (BPH) tissue 23,26 . In contrast, HCA carcinogens are known to be detoxified by gluathione Stransferases (GSTs) and possibly also NADPH-quinone oxidoreductase (NQO1) [22][23]25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions have also been shown between genes and diet in measures of DNA damage, 70 prostate cancer risk and levels of the glutathione s-transferase alpha. 71,72 Cognitive decline APOE has been identified as a susceptibility gene for Alzheimer's disease, with the e4 variant increasing risk for disease. The Risk Evaluation and Education for Alzheimer's Disease (commonly known as REVEAL) study examined how knowing APOE e4 status impacted behavior change in the adult offspring of parents with Alzheimer's disease.…”
Section: Cancermentioning
confidence: 99%
“…Other authors have demonstrated gene-diet-dependent effects on reduced DNA damage (Palli et al 2004), reduced prostate cancer risk (Steinbrecher et al 2010), and increased levels of GST alpha (Lampe et al 2000). These interactions among genotype, cruciferous vegetables, and lung cancer risk have also been confirmed in a systematic analysis (Lam et al 2009).…”
Section: Personalized Nutrition: If Not Now When?mentioning
confidence: 99%